Development of climate friendly cooling technologies: Trends and driving factors, 1990-2019 - Sheng Zhong (Asian Development Bank Institute (ADBI), 2023)
Cooling is an important area for which there is a rapidly increasing demand, but it accounts for a sizeable portion of electricity consumption and generates negative environmental externalities. Technological change directed towards environmental sustainability is essential for cooling to play a role in sustainable development pathways. This paper seeks to characterize important empirical patterns regarding climate friendly cooling technologies. This is mainly based on a patent search strategy following the Organisation for Economic Co-operation and Development (OECD) guidelines on environmental technologies. We identify 118,396 patent families in this field over the period 1990-2019, and the top five innovative economies, i.e., the People's Republic of China (PRC), Germany, Japan, the Republic of Korea, and the United States, accounting for 90.4% of total technologies. Global innovation in this field, dominated by Japan in the early years, has achieved a rapid growth since 2005, which was primarily driven by the PRC. The United States is the innovation leader in terms of scientific impact. Japan is found to be exclusively specialized in a single cooling field, whereas the other major economies have more diversified innovation portfolios. This suggests newcomers to this field should develop innovations that match their national needs and core competences. Using an index decomposition technique, this paper further quantifies the drivers of innovation in this field. Despite different GDP effects, the decomposition results highlight the crucial role of prioritizing cooling technologies and enhancing R&D intensity and productivity.
Keywords: C65; O30; O38; Q50; 330; patents; technological development; climate friendly cooling; LMDI decomposition